Net Neutrality: Netflix vs. Comcast's Case and the Brazilian Internet Civil Mark (Law, State and Telecommunications Review, 2015)
Purpose ”“ The main goal of the article is to address how Brazil has progressed in favor of net neutrality. Comcast vs. Netflix case is used as an example to compare the actions took by the United States and Brazil concerning this theme.Methodology/approach/design ”“ The text follows the problem-driven approach to infer some conclusions about the practices that has been adopted by the United States and Brazil.Findings ”“ It has been verified that Brazil is on the vanguard of internet governance as far as net neutrality is concerned.Practical implications ”“ The article can allow for a vast comprehension about net neutrality on par with the Brazilian Internet Civil Mark.